An Industrial quality control study on Metro Container Corporation - Dela Cruz, Carrel A.; Galicia, Mary Jane D.C.; Sarmiento, Rodeliza L. (Diliman, Quezon City College of Engineering, 2004)
Metro Container Corporation, or Metro Can, is a manufacturing company that produces various types of tin cans. Among all the products that they manufacture, the most number of rejects and the largest percentage of annual sales comes from the production of motor oil cans. The data of the company showed that almost 98% of motor oil cans produced are that of 401 and hence, the study focused mainly on the production of 401 products. From the Statistical tools and techniques used, such as Pareto Chart, Check Sheet, Streamline Diagnosis Chart, Ishikawa Diagrams, P-Chart and OC curves, it was found out that the major causes of rejects are misprint, side weld defects, seam bottom defects and scratches. From the months of January to July 2003, the Pareto Chart and Check Sheet showed that the largest number of defects was caused by misprint, though it dropped significantly starting from the month of March. This was because the company was able to do some corrective measures regarding misprint. The next biggest contributor to number of rejects were side weld defects, which was noticed to constantly produce significant amount of defective products. It was also noticed that most of the rejects due to flanging and seaming are just carried over from the defective items that were not immediately identified after the side welding process, thus, the study focused mainly on side weld defects. Using the tools and techniques mentioned earlier, the group was able to come up with recommendations that could improve the existing system of a company. A sampling procedure based on MIL STD 105E for attributes was proposed in replacement of the current sampling procedure used. The group also recommended that the maintenance team shall check and ensure proper condition of the machines before and after every shift to minimize machine stoppages. To be able to conduct sampling regularly, it was recommended that the Quality Inspector share the work with other operators. Lastly, the group recommended that the company shall conduct proper training of workers and briefings regarding the correct ways of handling the materials, be it raw or finished products.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control.
Keywords: Metro Container Corporation; Container industry; Quality control